Bone marrow mesenchymal stem cell-secreted exosomes carrying microRNA-125b protect against myocardial ischemia reperfusion injury via targeting SIRT7 - Qi Chen; Yu Liu; Xueyan Ding; Qinfeng Li; Fuyu Qiu; Meihui Wang; Zhida Shen; Hao Zheng; Guosheng Fu (Molecular and Cellular Biochemistry, 2020)
MicroRNA-125b (miR-125b) reduces myocardial infarct area and restrains myocardial ischemia reperfusion injury (I/R). In this study, we aimed to investigate the effect of bone marrow mesenchymal stem cell (BMSC)-derived exosomes carrying miR-125b on I/R rats. The myocardial I/R model in rats was constructed by ligation of the left anterior descending coronary artery (LAD). Rats were randomly divided into I/R and Sham group. Lv-cel-miR-67 (control) or Lv-miR-125b was transfected into BMSCs. Exosomes were extracted from transfected BMSCs, and separately named BMSC-Exo-67, BMSC-Exo-125b, and BMSC-Exo. MTT assay and flow cytometry were used to detect the viability and apoptosis of I/R myocardium cells, respectively. The expression of cell apoptosis proteins and the levels of inflammatory factors were examined by Western blot and ELISA assay, respectively. The target relationship between miR-125b and SIRT7 was predicted by using StarBase3.0, and was confirmed by using dual-luciferase reporter gene assay. qRT-PCR, immunohistochemistry staining, and Western blot were used to evaluate the expression of SIRT7 in myocardium tissues in I/R rats. BMSC-derived exosomes were successfully isolated and identified by TEM and positive expression of CD9 and CD63. The expression of miR-125b was down-regulated in I/R myocardium tissues and cells. BMSC-Exo-125b significantly up-regulated miR-125b in I/R myocardium cells. The intervention of BMSC-Exo-125b significantly increased the cell viability, decreased the apoptotic ratio, down-regulated Bax and caspase-3, up-regulated Bcl-2, and decreased the levels of IL-1β, IL-6, and TNF-α in I/R myocardium cells. SIRT7 was a target of miR-125b, and BMSC-Exo-125b significantly down-regulated SIRT7 in myocardium cells. In addition, the injection of BMSC-Exo-125b alleviated the pathological damages and down-regulated SIRT7 in myocardium tissues of I/R rats. BMSC-derived exosomes carrying miR-125b protected against myocardial I/R by targeting SIRT7.